2018
DOI: 10.1016/j.ijdevneu.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal antioxidant supplementation and/or exercise practice during pregnancy on postnatal overnutrition induced by litter size reduction: Brain redox homeostasis at weaning

Abstract: Prenatal and early postnatal environments can permanently influence health throughout life. Early overnutrition increases the risk to develop chronic diseases. Conversely, the intake of flavonoids and exercise practice during pregnancy seem to promote long-term benefits to offspring. We hypothesized that benefic interventions during pregnancy could protect against possible postnatal neurochemical alterations caused by overnutrition induced by reduced litter size. Female Wistar rats were divided into four group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 86 publications
2
9
0
Order By: Relevance
“…Our results show for the first time that early life consumption of NAC decreased the deleterious metabolic effects caused by HFD feeding of the adult. Our data are in accord with previous study demonstrating the benefits of polyphenols antioxidants given to healthy rats, on the response of offspring to overfeeding, induced by reducing litter size [12]. In addition, flavonoids given to healthy mice during pregnancy, improved the antioxidant capacity of the adult offspring [61].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results show for the first time that early life consumption of NAC decreased the deleterious metabolic effects caused by HFD feeding of the adult. Our data are in accord with previous study demonstrating the benefits of polyphenols antioxidants given to healthy rats, on the response of offspring to overfeeding, induced by reducing litter size [12]. In addition, flavonoids given to healthy mice during pregnancy, improved the antioxidant capacity of the adult offspring [61].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, flavonoids given to healthy mice during pregnancy, improved the antioxidant capacity of the adult offspring [61]. Our results, as well as the above mentioned publications [12,62] demonstrated that maternal antioxidant supplementation might be beneficial for offspring health, even when given to healthy mothers, which are not expected to experience oxidative stress.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Naringenin (50 mg/kg) was suspended in sunflower oil (1 ml/kg), which was used as vehicle, and administered by gavage 5 d/week (Monday to Friday) for the 3 weeks of pregnancy to treated rats. The dose was defined according to its neuroprotective action (62,64) and did not interfere on pregnancy rate, gestational weight gain, litter size or weight at birth, as shown previously (3) .…”
Section: Animals and Reagentsmentioning
confidence: 99%
“…This concept evolved from Barker's studies on the thrifty phenotype, or Barker's hypothesis (Barker et al, 1989). Our group already showed how several different interventions may influence the offspring health when applied during pregnancy, such as Caloric Restriction (CR) (Stone et al, 2019), food restriction (FR) (Stone et al, 2016), high‐salt diet (Stocher et al, 2018), polyphenol supplementation (August et al, 2018), and swimming exercise (August et al, 2018; Klein et al, 2018, 2019; Marcelino et al, 2013).…”
Section: Introductionmentioning
confidence: 99%